Avaliação do Efeito Fotodinâmico sobre o Crescimento in vitro de Pythium insidiosum - Pires, Layla [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Photodynamic Therapy (PDT) is a therapeutic method which employs a photosensitizer and light to cause cellular death. The chemical compounds have low or none toxicity for hosts cells. Under the incidence of light, in an appropriated wavelength, these chemical compounds produce reactive oxygen which affects the biomolecules of the target-cells. The specific illumination of the affected area increases the selectivity of the therapy, since the photodynamic process occurs only in the irradiated area. Pythiosis, for instance, is a life-threatening emerging disease caused by a fungus-like organism called Pythium insidiosum. The disease occurs in man and other animals, being mostly observed in horses. Human pythiosis may present as ophthalmic, cutaneous-subcutaneous and systemic forms of lesions. Due to the fact that P. insidiosum is not a true fungus, it is refractory to most antifungal drugs and the treatment of the disease is difficult. Extensive surgery procedures, such as limb amputation, are the treatment of choice, however relapses may occur frequently. Although not totally effective, the use of immunotherapy associated to surgery have shown some results. Considering that pythiosis is an emerging disease few explored in its etiological and therapeutic aspects, which are limited and few effective, it is of great importance to encourage the development of researches for new strategies of treatment. In this sense, it was evaluated the effect of PDT on in vitro growth of the pathogen employing two chemical compounds as photosensitizer, porphyrin and chlorine, at different concentrations in combination with several energetic dosages. Porphyrin showed inhibition of growth at 25mg/mL with 100J/cm2 of energetic dosage and chlorine showed similar results employing low concentrations (0,7, 1,0 and 1,3mg/mL) with 70J/cm2 of energetic dosage... (Complete abstract click electronic access below)

A terapia fotodinâmica é uma modalidade terapêutica que combina o uso de uma substância fotossensibilizadora e luz para causar a morte celular. As drogas utilizadas nesse processo são conhecidas como fotossensibilizadores e possuem pouca ou nenhuma toxicidade às células do hospedeiro. Sob iluminação, estas substâncias produzem espécies reativas de oxigênio capazes de promover danos a biomoléculas da célula-alvo. A iluminação precisa da área alvo aumenta a seletividade da terapia, uma vez que o processo fotodinâmico ocorre somente na área irradiada. A Pitiose, por exemplo, é uma doença causada por um micro-organismo semelhante a fungo denominado Pythium insidiosum. Acomete o homem e animais, sendo mais freqüentemente observada na espécie eqüina. No homem, a doença pode se manifestar nas formas oftálmica, cutâneo-subcutânea ou sistêmica. Por não ser um fungo verdadeiro, o agente não responde à maioria das drogas antifúngicas disponíveis, tornando difícil o tratamento da doença. Procedimentos cirúrgicos extensos, como amputação de membros, são indicados; porém as recidivas são freqüentes. A utilização de imunoterápicos em associação ao debridamento cirúrgico tem mostrado algum resultado, entretanto não totalmente eficazes. A pitiose é uma doença emergente, pouco explorada nos aspectos etiológicos e terapêuticos, os quais são limitados e pouco efetivos, dessa forma, se faz necessárias pesquisas para o desenvolvimento de novos tratamentos. Neste sentido, o presente trabalho avaliou o efeito da PDT no crescimento in vitro do patógeno utilizando dois fotossensibilizadores, porfirina e clorina, com diferentes concentrações e diferentes dosagens energéticas. Nos ensaios utilizando a porfirina como fotossensibilizador, os melhores resultados foram obtidos para 25mg/mL da droga e 100J/cm2. Nos ensaios com a clorina, os resultados foram semelhantes... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Fungos; Biotecnologia; Fototerapia